Plate-plume tectonics as an integrated mechanism of geodynamic development of the tectonosphere of Ukraine and adjacent regions - O . B. Gintov (Геофизический журнал, 2019)
A progress of geodynamic processes in Early Precambrian of the Ukrainian Shield (USh) has been considered. Based on the known data on plate- and plume-tectonic processes of Phanerozoic the following problems have been investigated: 1) what trajectories of material flows in Precambrian mantle might occur; 2) what was an interaction of plumes and regular mantle convection; 3) the time of existence of plumes and are they permanent or pulsating; 4) the time of beginning of Precambrian geodynamic processes comparable with Phanerozoic ones. It has been shown taking as examples the Ukrainian and the Canadian shields that present-day thermochemical and dynamic processes do not completely delete geological-geophysical features of ancient zones of subduction and plumes in solid lithosphere and adjacent areas of mesosphere preserved since Early Precambrian. The Earth crust of these shields was intensely reprocessed by granitization and basification comparable with activity of hot points that were more developed than now. Within the area of USh these processes were the most active in the interval 2,0±0,2 Ga. Two of stages of geodynamic evolution of the USh within the limits of the Bug-Middle Dnieper-Periazov and Volyn-Podolian parts, superimposed in time, have been studied. Comparison of materials of geologic-geophysical mapping of this territory with the data of deep seismic sounding (DSS) and seismography allows refining geodynamic model of the Volyn-Podolian part of the USh along the trans-sect Eurobridge-97 composed earlier. Tectonophysical justification of necessity to include pulsating plumes with which formation of the Korsun-Novomyrgorod and Korosten plutons of gabbro -anorthosites and rapakivi was particularly associated to geodynamic process has been given. Comparison of models of subduction-collision processes within the limits of the USh and the Superior Province (Canada) has shown that independent approaches to solving geodynamic problems give relative results. The materials obtained on the USh do not exhaust all the possible episodes of its Neoarhean –Proterozoic geodynamic development. Trailing of super-modern DSS geo-travers along the axial part of the USh is required for their study.